Design and implementation of Lifesaving Virtual Blood Bank - B., Satish Kumar Reddy; Y., Bhaskar Rao (International Journal of Psychosocial Rehabilitation, 2020)
Computerized Blood Bank is an affiliate function that puts into a shared forum volunteer blood donors, disabled and elderly, who are in need of blood. The aim is to fulfill every nation-wide blood demand with good mobile apps and motivated people who wish to donate blood.The suggested study intends to overcome such a hurdle of communication by using the minimal cost & economic power of the Raspberry Pi B+ kit to provide a direct connection between the sponsor and the customer. Only Micro USB of 5V and 2A power supply are required. Full interaction is via SMS (short messaging service) and is compatible with all cellular types. "Unmanned Blood Bank" is a project that places the blood donations & others in need of blood on a shared forum.The goal of this project is to help the people who need donors who are interested in donating blood and to provide it within the appropriate time frame.Unmanned Blood Bank is seeking to support the victims who need blood. The suggested work investigates the use of a GSM-based Smart Card CPU-Raspberry Pi B+ Package to find blood donors. The dream is to be "Every Citizen’s hope in finding a willing blood donor."